MicroRNAs regulate the epithelial–mesenchymal transition and influence breast cancer invasion and metastasis. Issue 2 (February 2017) - Zhao, Min; Ang, Lin; Huang, Jin; Wang, Jin
MicroRNAs are small RNA molecules that play a major role in the post-transcriptional regulation of genes and influence the development, differentiation, proliferation, and apoptosis of cells and the development and progression of tumors. The epithelial–mesenchymal transition is a process by which epithelial cells morphologically transform into cells with a mesenchymal phenotype. The epithelial–mesenchymal transition plays a highly important role in tumor invasion and metastasis. Increasing evidence indicates that microRNAs are tightly associated with epithelial–mesenchymal transition regulation in tumor cells. In breast cancer, various microRNA molecules have been identified as epithelial–mesenchymal transition inducers or inhibitors, which, through different mechanisms and signaling pathways, participate in the regulation of breast cancer invasion and metastasis among various biological behaviors. The epithelial–mesenchymal transition–related microRNAs in breast cancer provide valuable molecules for researching cell invasion and metastasis, and they also provide candidate targets that may be significant for the targeted therapy of breast cancer.